The relationship between the nitric oxide synthase gene and the risk of hypertension defi ned according to ambulatory blood pressures - Candy, Geoffrey; Badenhorst, Danelle; Libhaber, Elena; Sareli, Pinhas; Norton, Gavin R.; Brooksbank, Richard; Woodiwiss, Angela J. (SA Heart Journal, 2017)
Although nitric oxide (NO) plays an important role in blood pressure (BP) control, whether variation of genes involved in regulating the synthesis of NO infl uences BP is uncertain. As the heritability of BP is stronger for ambulatory than it is for conventional BP, we assessed the independent association of the well described functional exon 7 Glu298Asp variant of the eNOS gene with the presence of hypertension in 511 randomly selected normotensive control participants and 503 hypertensives with a diagnosis of hypertension confi rmed with 24-hour ambulatory BP profiles whilst off therapy. We also assessed the relationship between eNOS genotype and 24 hour ambulatory BP. Comparisons of genotype and allele frequencies indicated a lack of association of the exon 7 Glu298Asp gene variant with hypertension (Odds ratio of genotype predicting the presence of hypertension=0.97, confidence interval=0.70-1.30, p=0.92). However, patients with the Glu/Glu genotype of the Glu298Asp variant (n=424) had increased 24-hour systolic and diastolic blood pressures (152±1/97±1 mm Hg) in comparison to patients heterozygous for the Glu298Asp variant or homozygous for the 298Asp allele (n=79) (145±1/94±1 mm Hg, p‹0.005 for systolic BP and p‹0.001 for diastolic BP after multiple adjustments including age, gender, body mass index and the presence of diabetes mellitus). Differences in systolic and diastolic BP between genotype groups were noted during the day as well as at night. The association of eNOS genotype with ambulatory BP translated into an increased risk of more severe grades of hypertension in patients with the Glu/Glu genotype (grade II and III vs. grade I, Odds ratio=2.20, confidence interval=1.34-3.59, p‹0.0002). In conclusion, a functional gene variant (Glu298Asp) at the eNOS locus contributes ~1.4-2.5% to the variation in ambulatory blood pressure within hypertensives, but is not associated with the presence of hypertension in patients in whom the diagnosis has been confirmed by 24-hour ambulatory BP values. The relationship between eNOS genotype and 24-hour ambulatory BP and the severity of hypertension warrants further study.